A Significant Role of Rotavirus in Acute Gastroenteritis in Infants and Young Children - Muzief Munir; S. Salendu-Warovw; I. S. Karundeng (Paediatrica Indonesiana, 1983)
A study of the role of rotavirus in acute gastroenteritis in infants and children was conducted in an attempt to find out the magnitude of its problems. It was found that the majority of cases with acute diarrhea was caused by rotavirus, only 8% were bacteriial gastroenteritis while the remaining one third of unknown origin. The clinical course of rotavirus gastroenteritis seemed to be a dysentery like diarrhea with an acute onset of watery diarrhea, associated with fever and vomiting. These findings indicate that a further extensive study is needed and that the regimen of treatment of dysentery-like diarrhea should be reevaluated.